Type I osteogenesis imperfecta: a nonfunctional allele for pro alpha 1 (I) chains of type I procollagen. - Barsh, G S (1982)
Type I osteogenesis imperfecta (OI) is a dominantly inherited disease characterized clinically by bone fractures during childhood, blue sclerae, and frequent hearing loss accompanied by a decreased content of type I collagen in bone and skin. Cultured skin fibroblasts from three individuals affected with the disease produce half-normal levels of type I procollagen, a disulfide-bonded trimer that contains two pro alpha 1(I) chains and one pro alpha 2(I) chain. In normal cells, pro alpha 1(I) and pro alpha 2(I) are synthesized in a 2:1 ratio and only assembled molecules are secreted. In contrast, the OI cells contain equimolar amounts of pro alpha 1(I) and pro alpha 2(I), which suggests that trimer assembly and secretion are limited by the level of pro alpha 1(I) synthesis. The "extra" pro alpha 2(I) in the OI cells is in a nondisulfide-bonded configuration and is not secreted but apparently contributes to an increased level of intracellular degradation. Thus, decreased production of type I procollagen in these patients is the result of decreased synthesis of pro alpha 1(I). These results suggest that the stoichiometry of pro alpha chains in type I procollagen is determined by the conformation of the chains rather than the ratio in which they are synthesized, that molecules containing more than a single pro alpha 2(I) chain are not assembled, and that the production of this heteropolymeric molecule may be effectively regulated by controlling the synthesis of only one of the subunits.